The relationship between economic indicators and Malaysian Real Estate Investment Trust (MREIT) / Nurizzati Marso and Nur Amalina Mat Jamil - Marso, Nurizzati; Mat Jamil, Nur Amalina (Faculty of Business and Management, 2014)
The aim of this study is to investigate the relationship between economic indicators namely the stock market, interest rate and inflation rate to Malaysia real estate investment trusts return. The study used Simple Linear Regression and Multiple Linear Regression method in order to find the relationship among those variables. The monthly closing price of Malaysia real estate investment trusts index which is retrieved from Datastream database is collected from 1st February 2008 until 31st March 2014. The data is used as it is the best proxy that represents the Malaysia real estate investment trusts sector in the country. From the result, it is revealed that all the economic indicators tested have significant positive relationship towards Malaysia real estate investment trusts return. It means that the relationship between these economic indicators and Malaysia REITs exists. These results would contribute to the literature in related areas and give people a view on current condition of the Malaysia real estate investment trusts sector.